PROXIMATE AND PHYTOCHEMICAL SCREENING: EVALUATION OF MINERALS AND VITAMIN COMPOSITION OF (hypoestes rosea) PLANT HARVESTED IN CALABAR, CROSS RIVER STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
The positive values of medicinal plants cannot be over emphasized. Therefore, hypoestes rosea (hr) has been found to be useful in traditional health practice for the treatment and management of several illnesses such as hypertension, malaria, skin diseases, and diabetes mellitus. The plant materials were collected washed and blended then analyzed using standard methods. The ash content, fat, protein, fiber, moisture, and carbohydrate (mg/100ml) were; 8.50 Â± 0.25, 8.60 Â± 0.074, 2.90 Â± 0.095, 12.11 Â± 0.154, 62.50 Â± 2.50, 9.06 Â± 1.73 respectively. For the phytochemical analysis (mg/100ml) the following were determined involving saponins, terpenoids, flavonoids and alkaloids were; 17.86 Â± 0.14, 3.30 Â± 0.30, 11.935 Â± 0.065, 4.34 Â± 0.36 respectively. Result of vitamin composition showed that hypoestes rosea sample contains 0.033+ 0.001 (mg/100g) of vitamin A, 0.065+ 0.0005 (mg/100g) of vitamin B12, 0.0455+0.0005 of vitamin C, and 0.1655+ 0.0005 of vitamin E respectively.  It was observed that a 100g of hypoestes rosea was high in vitamin C (0.0455+ 0.0005) followed by vitamin B12 (0.0365+0.0005). Also, the result of mineral composition showed that Hypoestes rosea contains 0.035 + 0.00495 of Fe, 0.225 + 0.0005 of Zn, 1.045 + 0.00495 of K, 2.12 + 0.0 of Na, 0.26 + 0.01 of CL- respectively. The findings provide evidence that the extract of the plant contained some phytochemicals, thus suggested the presence of bioactive compounds which justifies their use in traditional medicines for the treatment of different diseases and also contribute greatly to human nutritional requirement for normal growth and development.
Keywords: Hypoestes rosea. Proximate Analysis., phytochemical., flavonoid., Alkaloids., Saponin